Structural and Semantic Realizations of Phrase Scheme “not + infinitive + same” in Newspaper and Literary Texts - L. A. Zolotareva; Tczianxin Zhen (Научный диалог, 2023)
The article deals with the structural and semantic features of the phrase scheme “not + infinitive + same” associated with the functioning of the structure in newspaper and literary texts. The study showed that in the structural composition, not only constant components (not, infinitive, same), but also optional ones are possible: after all, well, indeed. They retain their semantic and pragmatic properties; when used with a phrase scheme, they help to convince the interlocutor. In the context, the phrase scheme “not + infinitive + same” can be combined with other phraseologized structures or repeated several times to strengthen the argument. It is possible to use this phrase scheme as part of lexical phraseological units. When describing the semantic aspect, additional meanings were revealed in various contextual uses. In fiction and newspaper texts, the phrase scheme is characterized by colloquial stylistic coloring, its functioning is distinguished by the composition of constructions, the semantic characteristics of the infinitive. The constructions with the most frequent verbs in fiction and newspaper discourses are also considered in the article. The material was texts from the Russian National Corpus.